Development of Digestive Enzyme of Patin Pangasius hypohthalmus Larvae - I. Effendi; D. Augustine; . Widanarni (Jurnal Akuakultur Indonesia)
Culture of patin Pangasius hypophthalmus especially larval rearing  very depends on the supply of natural food as energy source.  Artemia is the main natural food for fish larvae as a starter food, but its price is high.  To reduce production cost, farmers tend to reduce the feeding frequency and shorten  the Artemia feeding period.  Altering feeding regime however may reduce fry quality. This relate to the availability of digestive enzymes.  The objective of this study was  to examine digestive enzymes activity in patin larvae fed with  different feeding regime.  By shorten feeding period with Artemia to 2-4 days and Tubifex,substitution, the enzymes activity of protease, lipase and amylase were revealed similar pattern   The enzymes activity tends to increase and reach the peak at day 7 , and decrease later on until day 15 after hatching.  Survival rate of fish were varied for each treatment, and the highest survival rate was obtained when larvae were fed by Artemia for 8 days.  Blood worm were not fully digested by patin larvae at early stage.